2014
DOI: 10.1111/jns.12098
|View full text |Cite
|
Sign up to set email alerts
|

Corneal confocal microscopy detects small fiber damage in chronic inflammatory demyelinating polyneuropathy (CIDP)

Abstract: Chronic inflammatory demyelinating polyneuropathy (CIDP) is an autoimmune-mediated peripheral neuropathy with multifocal involvement. Reliable biomarkers for diagnosis, disease progression, and treatment response remain to be developed. We assessed the utility of corneal confocal microscopy (CCM) as a diagnostic marker for CIDP in 16 patients. CCM parameters including corneal nerve fiber density (NFD), nerve fiber length, number of main nerve trunks, number of nerve branches, nerve tortuosity, and dendritic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 26 publications
3
29
0
1
Order By: Relevance
“…Our findings confirm recently published data demonstrating a reduction in CNF parameters in a cohort of 16 patients with CIDP 39. Our data are further supported by a previous study showing intraepidermal nerve fiber loss40 and unmyelinated nerve fiber degeneration in sural nerve biopsies41 of patients with CIDP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings confirm recently published data demonstrating a reduction in CNF parameters in a cohort of 16 patients with CIDP 39. Our data are further supported by a previous study showing intraepidermal nerve fiber loss40 and unmyelinated nerve fiber degeneration in sural nerve biopsies41 of patients with CIDP.…”
Section: Discussionsupporting
confidence: 92%
“…However, studies exploring corneal involvement in CIDP are limited and conflicting to date. While corneal sensitivity was normal,21 a recent study using CCM in 16 patients with CIDP demonstrated corneal nerve fiber (CNF) loss 22. CCM can also quantify the presence and density of Langerhans cells in Bowman's layer of the cornea in patients with diabetes 23.…”
Section: Introductionmentioning
confidence: 99%
“…There was a correlation between the corneal nerve fiber loss and the severity of diabetic polyneuropathy [54,55]. Currently, many other diseases are being investigated, for example, chronic migraine [56], Wilson disease [57], chronic inflammatory demyelinating polyneuropathy [58] or amyotrophic lateral sclerosis [59], demonstrating signs of neuropathy detected by CCM. Compared with other tools, the diagnostic efficacy of CCM is comparable or even higher than the quantification of the IENFD [48 & ], but has not been compared with QST in larger cohorts so far.…”
Section: Clinical Applicationsmentioning
confidence: 97%
“…Chronic inflammatory demyelinating polyneuropathy has been labelled as a condition which primarily affects large myelinated fibres; however, recent studies have revealed significant small sensory nerve pathology . Schneider et al showed a significant reduction in sub‐basal nerve fibre density and length with an increase in dendritic cell density in patients with chronic inflammatory demyelinating polyneuropathy.…”
Section: Corneal Confocal Microscope In Other Peripheral Neuropathiesmentioning
confidence: 99%